Review: Neurochemical Aspects of Mental Health and Neurological Diseases - Umaru, Isaac John; Innocent, Nwofor; Umaru, Kerenhappuch Isaac (African Journal of Biochemistry and Molecular Biology Research, 2024)
Neurochemistry is the study of chemicals, including neurotransmitters, hormones, and other molecules, that influence the function and behavior of the nervous system. This field has evolved significantly since the early 20th century, driven by key discoveries and technological advancements such as Neurotransmitters and Mental Health, "Neurotransmitters like serotonin, dopamine, and norepinephrine are fundamental in regulating mood, cognition, and behavior. Disruptions in these systems are implicated in various psychiatric disorders". Also, Neurotransmitter Imbalances and Mental Disorders: this is the Alterations in neurotransmitter levels, such as serotonin and dopamine, are associated with the symptoms of depression and schizophrenia". Then the GABAergic dysfunction is linked to anxiety disorders, highlighting the role of inhibitory neurotransmission in mental health". As well as Role of Neurochemicals in Specific Disorders: where low serotonin levels are commonly found in individuals with depression, leading to the development of SSRIs as a treatment". The review also look into Schizophrenia which is associated with both hyperactivity and hypoactivity of dopamine pathways, which influences treatment strategies", as well as the Neurochemical Pathways and Mechanisms: The HPA axis plays a critical role in the stress response, and its dysregulation which is linked to mood disorders". Dopaminergic pathways, including the mesolimbic and nigrostriatal systems, are essential for reward and motor control" as well as the Neurotransmitter Receptors and Transporters, Serotonin receptors, such as 5-HT1A, are critical in mood regulation and are targeted by many antidepressants". The central point of disorder "Dopamine transporters are involved in the re-uptake of dopamine and are implicated in disorders like ADHD and addiction". Thus, Neuroinflammation and Mental Health: which Increased neuroinflammation is associated with depression, with elevated pro-inflammatory cytokines observed in affected individuals", "Microglia and their role in neuroinflammation and psychiatric disorders are all the key area of the research."